2018
DOI: 10.20902/ijptr.2018.11309
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-like effect of derivatives of Pyrimidine, Pyrazole, Isoflavones, Pyridine, Oxazolopyrimidine and Oxazole on acceleration of Vegetative growth of Flax

Abstract: The comparative analysis of the stimulating effect of low molecular weight heterocyclic compounds, derivatives of pyrimidine, pyrazole, isoflavones, pyridine, oxazolopyrimidine, oxazole and plant hormones auxins IAA (1H-Indol-3-ylacetic acid) and NAA (1-Naphthylacetic acid) on germination of seeds and growth of seedlings of flax (Linum usitatissimum L.) cultivars Ukrainian 3 and Svitanok was conducted. The specific auxin-like stimulating effect of chemical heterocyclic compounds on the basic processes of flax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…To solve this problem, culture media are saturated with various additives of natural or synthetic origin. Recently, synthetic low-molecular-weight heterocyclic compounds represented by pyridine, pyrimidine, pyrazole and oxazole derivatives have been under extensive research due to their high e ciency at low concentrations and lack of toxic effects on plant and animal cells, which ensures environmental safety [26,27,28,29,30,31]. To the best of our knowledge, in this study we examined the effect of synthetic plant growth regulators Ivin, Methyur and Kamethur on fungal growth is the rst time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To solve this problem, culture media are saturated with various additives of natural or synthetic origin. Recently, synthetic low-molecular-weight heterocyclic compounds represented by pyridine, pyrimidine, pyrazole and oxazole derivatives have been under extensive research due to their high e ciency at low concentrations and lack of toxic effects on plant and animal cells, which ensures environmental safety [26,27,28,29,30,31]. To the best of our knowledge, in this study we examined the effect of synthetic plant growth regulators Ivin, Methyur and Kamethur on fungal growth is the rst time.…”
Section: Discussionmentioning
confidence: 99%
“…Among all studied cultures, P. ostreatus strains 551 and 1685 were more receptive to positive assimilation of all investigated compounds used in nanomolar concentrations. However, the growth-stimulating activity of the synthetic plant growth regulators Ivin, Methyur and Kamethur was previously established for various crops [28,29,30,32,33,34]. In general, concentrations of 10 − 5 , 10 − 6 and 10 -7 M of these synthetic plant growth regulators showed the highest growth-regulating effect [28, 29,30,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxazole and its derivatives are used in treatment of various types of illness [8] . Oxazole shows numerous biological activities such as anti-bacterial [9,10] , antifungal [11,12] , agonist of free fatty acid receptor (GPR40) [13] , highly selective histone deacetylase 6 (HDAC6) [14] , anticancer [15,16] , vegetative growth factor [17] , anti-tubercular, anti-leishmanial [18] , antiprotozoal [19] and anti-inflammatory [20] . Apart from these pharmacological activities, oxazole derivatives can also be used as anti-corrosive agent for stainless steel, dyes [21] , anti-ageing [22] , antioxidant [23] , metabolism enhancing agent [24] , pesticides and herbicides [6] .…”
Section: Pharmacological Activities Of Oxazolementioning
confidence: 99%
“…Kukhar Institute of Bioorganic Chemistry and Petrochemistry of National Academy of Sciences of Ukraine. Our numerous studies have shown that synthetic low molecular weight heterocyclic compounds, derivatives of pyrimidine have a high stimulating auxin-like and cytokinin-like effect on vegetative growth of various crops and increase their yield [30][31][32][33][34][35][36]. The advantages of using synthetic low molecular weight heterocyclic compounds are their high efficiency when used in very low concentrations and environmental safety due to lack of toxic effects on the human, animal and plant cells.…”
Section: Introductionmentioning
confidence: 99%